Impact of Asian financial crisis on Singapore residential property market. - Choo, Peck San. (2008)
In this report, we will assess the impact of the Asian Financial Crisis on the residential property market by examining how the market as a whole as well as the individual players had been affected during this period. The purpose of this report is to offer readers an insight into the effects of the currency crisis on the key players of the property market.